Study Interteks: Nubuat Tentang Mesias Dalam Yesaya. 9:5-6 Dan Kelahiran Yesus Dalam Matius. 1:20-23 - Priwinata, Agustinus Joni (Hymnos: Jurnal Teologi dan Keagamaan Kristen, 2025)
This study stems from confusion among churches and believers regarding who is referred to as the owner of the identity in Isaiah 9:5-6. This study aims to provide a deeper theological understanding, present sound teaching, and offer clarification for the confusion that arises regarding the identification of the character's identity in the text. To achieve this goal, this study uses a qualitative method which shows that Jesus is the owner of the identity described in Isaiah 9:5-6. The Gospel of Matthew theologically presents Jesus as the fulfillment of Isaiah's prophecy, particularly through His identity as Immanuel and His task to save His people from sin. Thus, the Messianic identity in Isaiah 9:5-6 finds its full fulfillment in Jesus. Through this intertextual study, a strong theological continuity between the Old Testament and the New Testament is revealed, which also confirms Jesus' identity as the promised Messiah. This research is expected to contribute to the development of intertextual studies in biblical theology and serve as a methodological reference for future intertextual research.